A gathering place : a Cape Light novel - Kinkade, Thomas, 1958-2012 (Kinkade, Thomas, 1958-2012. Cape Light novel, 2004)
Emily Warwick struggles to build a new relationship with Sara, the daughter she had given up for adoption two decades earlier, while dealing with her regret over their years apart and falling for newspaper publisher Dan Forbes.